Challenges of using ChatGPT in education: a digital pedagogy analysis - Murtiningsih, Siti; Sujito, Arie; Khin Soe, Khin (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research explains into the challenges posed by the increasing utilization of Chat generative pre-trained transformer (ChatGPT) in educational settings and proposes solutions to mitigate its potential negative impacts. The widespread adoption of artificial intelligence, exemplified by ChatGPT, in learning environments from elementary to higher education levels, raises concerns about its impact on critical thinking and reflection among students. Through a comprehensive literature review encompassing journals, scientific articles, news, and previous research, this study identifies the challenges associated with ChatGPT’s usage in education in the digital era. One significant challenge is the potential reduction in students’ ability to think critically and engage with reality due to overreliance on ChatGPT for assignments. Moreover, excessive dependence on ChatGPT risks diminishing the quality of human resources in education. To address these challenges, educators need to develop strategies to harness technological advancements effectively while fostering critical thinking skills in students. This research underscores the importance of equipping educators with the necessary skills to navigate the digital landscape and prevent academic dishonesty facilitated by ChatGPT.